Effect of Traditional Processing on the Nutritional Value of Some Legumes Seeds Produced in Sudan for Poultry Feeding - Ragab, H.I.; Kijora, C.; Ati, K. A. Abdel; Danier, J. (International Journal of Poultry Science, 2010)
Three local legumes seeds produced in Sudan were subjected in their two preliminary forms (whole and decorticated seeds) to different traditional processing and then analyzed for their composition of nutrients, minerals and amino acids. All seeds were found as good source of protein and digestible carbohydrate which support their supplementation approach in poultry diets. They show as well substantial quantities of minerals with an abundance of potassium and phosphorus. Amino acid analysis revealed high lysine, leucine, phenylalanine and arginine while sulfur-containing amino acids methionine and cystine were found deficient. Decortications and its further following processing were of worse effect mainly upon mineral contents, in addition to their impact on somewhat wastefulness of nutrient components owing to the inefficiency of dehulling, besides its cost effects. Roasting in spite of its negligible effects was inferior to both of germination and boiling of pre-soaked whole seeds with regard to amino acids. Boiling of presoaked whole seeds was found appropriate to all studied legumes while the 72 hour germination of presoaked seeds was superior to boiling for L. purpureus seeds.